2009
DOI: 10.1007/s12594-009-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of fluids in the formation of talc deposits of Rema area, Kumaun Lesser Himalaya

Abstract: Talc deposits of Rema area in the Kumaun Inner Lesser Himalaya are hosted within high magnesium carbonates of the Proterozoic Deoban Formation. These deposits occur as irregular patches or pockets mainly within magnesite bodies, along with impurities of magnesite, dolomite and clinochlore. Textures represent different phases of reactions between magnesite and silica to produce talc. Petrography, XRD and geochemistry reveal that the talc has primarily developed at the expense of magnesite and silica, leaving do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Then, our modelled seismic velocity values reduce between 5 and 15 km depths, suggesting a 10-20% drop in Vp, dVp, Vs and dVs and an increase in Vp/Vs by 10-14%, which could be explained in terms of the presence of meteoric water, aqueous uids and wet-sediments of the Eurasian plate. Several studies [32][33][34] (Boulier et al, 1991;Sachan et al, 2001;Sharma et al, 2008) have shown that the uids in the higher Himalaya and the MCT are dominantly carbonic whereas the uids in the Lesser Himalaya and the MBT are dominantly brines or syntectonic uids (Ojha and Srivastava, 2016). Between 15 and 20 km depth, a slight increase (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Then, our modelled seismic velocity values reduce between 5 and 15 km depths, suggesting a 10-20% drop in Vp, dVp, Vs and dVs and an increase in Vp/Vs by 10-14%, which could be explained in terms of the presence of meteoric water, aqueous uids and wet-sediments of the Eurasian plate. Several studies [32][33][34] (Boulier et al, 1991;Sachan et al, 2001;Sharma et al, 2008) have shown that the uids in the higher Himalaya and the MCT are dominantly carbonic whereas the uids in the Lesser Himalaya and the MBT are dominantly brines or syntectonic uids (Ojha and Srivastava, 2016). Between 15 and 20 km depth, a slight increase (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the study area has been subdivided into various sectors characterized by a common field and depopsitional characteristics. The pyroclastic ejecta in the area has been grouped in various sub groups based on clastsize, type of the clasts, and depositional features/structures associated with them (R.K. Sharma, 2000 [54], 2020 [55], 2022 [56] and Sharma 1992 [8], 2018 [57], Sharma and Pandit 1998 [58]). The main categories identified are…”
Section: Lithology and Nomenclature: (The Present Contributions Based...mentioning
confidence: 99%
“…compositionally banded vitric tuffs along with agglomerates of varying thickness and proportion dot the entire area. Felsic rocks including the compositionally banded (light and gray) tuffs together with andesitic and acidic flows as well as pumiceous flows of the acidic nature(Sharma and Pandit, 1998) [58], constitute an important litho unit in the area and forms parts of this category of deposit.The banded and pumiceous nature has a significant bearing on the mechanismof deposition. The salient characters of these rocks exposed in various areas are summarized for attempting a non-genetic classification.…”
mentioning
confidence: 99%
“…The most economically viable of these deposits are usually related to the metamorphic reaction between an Mg-carbonate infiltrated by a silica-rich hydrothermal fluid [18,20,21,37]. Intense fractures that increase the permeability of geological fluid flow generally develop near such deposits [18,20,21,37,38]. Investigating the formation temperature of talc can improve our understanding of its mineralization process.…”
Section: Implications For the Formation Of Mg-carbonate-hostedmentioning
confidence: 99%
“…The reaction has been theoretically calculated to occur at ≥150 ∘ C [5,35,36], but most geological studies have indicated that talc mainly forms at 250-400 ∘ C (e.g., [21,37,38]). For example, in the Saint-Barthélemy deposits in Switzerland, oxygen isotope thermometric calculations showed that talc mineralization occurred at about 300 ∘ C [21], which is consistent with fluid inclusion data (250-300 ∘ C) [39,40].…”
Section: Introductionmentioning
confidence: 99%